The neural underpinnings of reading skill in deaf adults - Emmorey, Karen; McCullough, Stephen; Weisberg, Jill (Brain and language, 2016)
•Skilled readers had greater activation in left IFG and MTG when reading for meaning.•Reading skill correlated with activity in left IT (orthographic-semantic interface).•Semantic task accuracy correlated with activity in left ATL (conceptual processing).•Phonological task accuracy correlated with activity in left IFG (articulatory coding).•Reading skill did not correlate with neural activity during the phonological task. We investigated word-level reading circuits in skilled deaf readers (N=14; mean reading age=19.5years) and less skilled deaf readers (N=14; mean reading age=12years) who were all highly proficient users of American Sign Language. During fMRI scanning, participants performed a semantic decision (concrete concept?), a phonological decision (two syllables?), and a false-font control task (string underlined?). No significant group differences were observed with the full participant set. However, an analysis with the 10 most and 10 least skilled readers revealed that for the semantic task (vs. control task), proficient deaf readers exhibited greater activation in left inferior frontal and middle temporal gyri than less proficient readers. No group differences were observed for the phonological task. Whole-brain correlation analyses (all participants) revealed that for the semantic task, reading ability correlated positively with neural activity in the right inferior frontal gyrus and in a region associated with the orthography-semantics interface, located anterior to the visual word form area. Reading ability did not correlate with neural activity during the phonological task. Accuracy on the semantic task correlated positively with neural activity in left anterior temporal lobe (a region linked to conceptual processing), while accuracy on the phonological task correlated positively with neural activity in left posterior inferior frontal gyrus (a region linked to syllabification processes during speech production). Finally, reading comprehension scores correlated positively with vocabulary and print exposure measures, but not with phonological awareness scores.